1994
DOI: 10.1093/carcin/15.11.2575
|View full text |Cite
|
Sign up to set email alerts
|

Selective induction of rat hepatic CYP1 and CYP4 proteins and of peroxisomal proliferation by green tea

Abstract: Rats were exposed to freshly prepared aqueous extracts of green tea (2.5% w/v) as the sole source of drinking water for 4 weeks. Hepatic cytochrome P450 activity was determined using chemical probes, showing selectivity for particular isoforms, and by immunoblot analysis employing polyclonal antibodies. Exposure to green tea gave rise to increases in the O-demethylation of methoxyresorufin and, to a lesser extent, in the dealkylations of ethoxyresorufin and pentoxyresorufin. An increase was also seen in lauric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…Induction of these enzymes by either naturally occurring or synthetic agents represents a promising chemopreventive strategy (5)(6)(7)(8). Green tea or green tea polyphenols have been shown to modulate various xenobiotic metabolizing enzymes, including GSTs, in animal studies and in in vitro systems (9)(10)(11)(12)(13)(14). Phase II enzyme induction by green tea polyphenols is generally believed to involve the activation of the mitogenactivated protein kinase pathway via the electrophilicmediated stress response, resulting in the activation of transcription factors that bind to antioxidant/electrophile response element located on many phase II genes (15).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of these enzymes by either naturally occurring or synthetic agents represents a promising chemopreventive strategy (5)(6)(7)(8). Green tea or green tea polyphenols have been shown to modulate various xenobiotic metabolizing enzymes, including GSTs, in animal studies and in in vitro systems (9)(10)(11)(12)(13)(14). Phase II enzyme induction by green tea polyphenols is generally believed to involve the activation of the mitogenactivated protein kinase pathway via the electrophilicmediated stress response, resulting in the activation of transcription factors that bind to antioxidant/electrophile response element located on many phase II genes (15).…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al 46) have reported that the pretreatment of rats with 0.5% green tea in their drinking water for 2 or 4 weeks did not produce a significant increase in cytochrome P450 content but enhanced microsome-mediated formation of non-toxic hydroxylated metabolites of AFB 1 by 2-3 fold. It has also been reported by Sohn et al 47) and Bu-Abbas et al 48) that rats administered GTE for 4 or 6 weeks displayed no significant increase in total cytochrome P450 content in the liver but did display a significant increase in O-dealkylase activity of ethoxyresorufin (CYP1A1), methoxyresorufin (CYP1A2) and pentoxyresorufin (CYP2B1). Table 2 indicates the suppressive effect of individual GTP on AFB 1 -induced CA.…”
Section: Discussionmentioning
confidence: 51%
“…However, the administration of EGCG 24 h before sacrifice did not result in a significant increase in cytochrome P450 content or GST activity (Ito and Ito, 2001). Sohn et al (1994) and Bu-Abbas et al (1994) have reported that rats administered GTE for 4 or 6 weeks displayed no significant increase in total cytochrome P450 content in the liver, but did display a significant increase in O-dealkylase activity of ethoxyresorufin (CYP1A1), methoxyresorufin (CYP1A2) and pentoxyresorufin (CYP2B1). Of the phase II enzymes, UDP-glucuronyltransferase was increased, but GST was not.…”
Section: Discussionmentioning
confidence: 99%